Do Subnational Fiscal Rules Foster Fiscal Discipline? : New Empirical Evidence from Europe - Kotia, Ananya (IMF Working Papers; Working Paper ;, 2016)
This paper studies how fiscal rules interact with the intergovernmental fiscal framework to foster fiscal discipline among European subnational governments. We use political variables describing the fiscal attitudes of the central government as instruments to obtain consistent estimates of the impact of subnational fiscal rules on fiscal balances. The results suggest that the discipline-enhancing effect of fiscal rules is weaker when there are large 'vertical fiscal imbalances' that is, large differences in revenue and spending assignments across the different levels of government. These findings imply that separate reforms to reduce excessive vertical fiscal imbalances complement a rules-based fiscal framework that is aimed at fostering fiscal discipline.